EKUITAS MEREK BATIK BANGKALAN DAN RESEPSI MASYARAKAT MADURA - Raniawati Rachman (Kanal: Jurnal Ilmu Komunikasi, 2015)
The purpose of this study was to analyze and describe brand equity of Batik Bangkalan and analyze public reception of Madura batik, as well as to analyze and describe the influence of brand equity Batik Bangkalan - Madura towards public reception in Madura. This type of research was quantitative with an explanatory approach. The population in this research was society of Bangkalan Madura. Samples were taken from consumers who visit the center of batik gallery in Bangkalan - Madura amount 100 respondents. The sampling technique used accidental sampling. Technique of analyzing data used multiple linear regression analyzes to examine a causal relationship between the causes variables namely brand equity (X) towards the effect variable namely reception of Madura society (Y). Hypothesis test results showed that simultaneously brand equity consists of brand awareness, brand association, perceived quality and brand loyalty linear effect on society reception. Partially, that significantly influence the public reception was brand awareness while brand association, perceived quality and brand loyalty has no significant effect. Variables that dominant influence on the public reception was brand awareness.